Genomic Signatures of Immune Activation Predict Outcome in Advanced Stages of Ovarian Cancer and Basal-Like Breast Tumors - Alcaraz-Sanabria, Ana; Baliu-Piqué, Mariona; Saiz-Ladera, Cristina; Rojas, Katerin; Manzano, Aránzazu; Marquina, Gloria; Casado, Antonio; Cimas, Francisco J.; Pérez-Segura, Pedro; Pandiella, Atanasio; Gyorffy, Balázs; Ocana, Alberto (Frontiers in Oncology, 2020)
Metastatic ovarian and basal-like breast cancers are unmet necessities as not curative therapies exist. Immunotherapy has shown to be active in several solid tumors, but particularly more in those where a pre-activated immune state does exist. In this work, we aim to identify biomarkers that could distinguish immune-activated tumors and predict response to therapies in ovarian and basal-like breast cancer, as well as their association with the level of tumor immune infiltration. We found that the combined expression of IFNG, CD30, CXCL13 and PRF1 correlated with better overall survival (OS) in advanced stage ovarian cancer. This was confirmed using an independent dataset from TCGA. Interestingly, we observed that this gene combination also predicted for better prognosis in ovarian tumors with low mutational load, which typically present a less activated immune state. Expression of IFNG, CD30, CXCL13 and PRF1 was associated with increased level of immune infiltrates (CD8+ T cells, dendritic cells and neutrophils) within the tumor. Similarly, the expression of IFNG, CD30, CXCL13 and PRF1, correlated with an increased OS and higher level of tumor infiltrates of most immune cells (B cells, CD8+ T cells, CD4+ T cells, neutrophils and dendritic cells) in basal-like breast cancer. In conclusion, our analysis identifies genes signatures with potential to identify immune activated ovarian and basal-like breast cancers with favourable prognosis and with a remarkable predictive capacity in tumors with low mutational burden.